Development of an advanced, efficient and green intermodal system with autonomous inland and short sea shipping - AEGIS. Issue 1 (1st July 2022) - Krause, S; Wurzler, L; Mørkrid, O E; Fjørtoft, K; Psaraftis, H N; Vilanova, M R; Zis, T; Coelho, N F; van Tatenhove, J; Raakjær, J; Kloch, K; Billesø, M B; et al.
Abstract: The European maritime transport policy recognizes the importance of the waterborne transport systems as key elements for sustainable growth in Europe. A major goal is to transfer more than 50% of road transport to rail or waterways within 2050. To meet this challenge waterway transport needs to get more attractive and overcome its disadvantages. Therefore, it is necessary to develop new knowledge and technology and find a completely new approach to short sea and inland waterways shipping. A key element in this is automation of ships, ports and administrative tasks aligned to requirements of different European regions. One main goal in the AEGIS project is to increase the efficiency of the waterways transport with the use of higher degrees of automation corresponding with new and smaller ship types to reduce costs and secure higher frequency by feeders and provide multimodal green logistics solutions combining short sea shipping with rail and road transport.